A new species of Rimboda Heller (Coleoptera, Curculionidae, Conoderinae, Othippiini) reared from Distylium racemosum Siebold & Zucc. in the Ryukyu Islands, Japan - Fujisawa, Yusuke; Lewis, Jake H.; Anzaldo, Salvatore S. (Zootaxa, 2025)
The genus Rimboda has hitherto contained six species from Indonesia, Malaysia, and Philippines. Here, Rimboda saekii Fujisawa & Lewis new species is described from specimens collected in the subtropical forests of Amami-Oshima, Tokunoshima, Okinawa-jima Island, and Ishigaki-jima Island, Japan. Specimens were reared from Distylium racemosum (Hamamelidaceae). The occurrence of Rimboda in southwestern Japan represents a significant northward extension in the known geographic range of the genus. We provide habitus photographs, a 3D model and illustrations of the male and female genitalia of R. saekii, as well as a checklist to the world species of Rimboda.